At Westonci.ca, we make it easy to get the answers you need from a community of informed and experienced contributors. Get immediate and reliable solutions to your questions from a community of experienced experts on our Q&A platform. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform.

Given: -3(x - 6) + 4(x + 1) = 7x - 14
Step 1: -3x + 18 + 4x + 4 = 7x - 14
Step 2: -3x + 4x + 18 + 4 = 7x - 14
Step 3: 1x + 22 = 7x - 14
Step 4: 1x - 1x + 22 = 7x - 1x - 14
Step 5: 22 = 6x - 14
I need help with this I am confused!?


Sagot :

Answer:

it is correct step

Step-by-step explanation:

it has no wrong in it b/c it subtract 1x from both side